Development and Evaluation of Vegan Egg using Soya Beans as Key Ingredient - E., Krithika; P. A., Raajeswari, (The Indian Journal of Nutrition and Dietetics, 2022)
Vegan diet is important for health and prevents many diseases. Egg contains the protein of highest biological value. Approximately the nutritional composition of one egg is 75 calories but 7 g of high quality protein, 5 g of fat and 1.6 g of saturated fat, along with iron, vitamins, minerals and carotenoids. Interest in alternative protein sources to those derived from animal, soya and wheat is on the rise. Pulses are rich in protein, carbohydrates, vitamins and minerals are low in fat. Soya bean pods generally contain one to three seeds within each one. The size of the soya seed ranges from 5-11 mm and seed weight from 120-180 mg/seed. They are generally a rich source of protein and filled with polyunsaturated fatty acids. With this background the present study was undertaken with the following objectives of developing a standardized vegan egg from a high protein source (soybean) to replace the egg protein. This study expounds developing techniques of vegan egg and preparing recipes for evaluation. The property of the selected protein source ensures the viscosity of the Vegan Egg developed. The soya bean vegan egg contains 658.3 kcal of energy, 35.5 g of carbohydrates, 63.3 g of protein, 29.1 mg of total fat, zero cholesterol, 483.3 mg of calcium, 525 mg of phosphorus, 108 mg of sodium, 1 mg of vitamin E and 0.30 mg of vitamin B6. Based on the type of flour used, the vegan egg is used for the suitable recipes. The study expounds developing techniques of vegan egg and preparing recipes for evaluation.